Protective Effects of Melatonin on Free Radical-Induced Oxidative Stress - Belvisi, Elisa; Carloni, Silvia; Tei, Monica; Alagna, Maria Gabriella; Santacroce, Antonino; Riccitelli, Marina; Bazzini, Francesco; Longini, Mariangela; Buonocore, Giuseppe; Perrone, Serafina; on behalf of the “Gruppo di Studio di Biochimica Clinica Neonatale della Società Italiana di Neonatologia” (Journal of Pediatric Biochemistry, 2016)
Melatonin is both a potent free radical (FR) scavenger and a broad-spectrum antioxidant. It seems to give useful effects in newborn disorders as has been shown for adults. The unbalance between prooxidant and antioxidant factors leads to oxidative stress (OS) and damage to biomolecules. OS is involved in the pathogenesis of many chronic diseases in adulthood, such as atherosclerosis, cancer, diabetes, rheumatoid arthritis, stroke and postischemic perfusion injury, myocardial infarction and cardiovascular diseases, chronic inflammation, septic shock, aging, and other degenerative diseases Nevertheless, there is growing evidence that OS is involved in the pathogenesis of many fetal and newborn diseases. The unbalance between a low-efficient antioxidant system and an overproduction of FR, especially in preterm babies, leads to the so-called FR-related disease of newborns, characterized by several cellular, tissue, and organ damage (kidney, retina, lung, bowel, and brain injury). Among antioxidants, melatonin (MLT) shows high antioxidant and anti-inflammatory properties: it is able to scavenge dangerous FR; it induces the production of antioxidant enzymes; it has no prooxidant effects; and it is safe. During the last decade, MLT has started to be considered as an attractive option to minimize as much as possible the sequelae from OS damage: in damaged lung tissue, MLT attenuates the hyperoxia-induced depletion of antioxidant enzyme activities and reduces proinflammatory cytokines; in animal model affected with necrotizing enterocolitis (NEC), MLT reduces tumor necrosis factor-α (TNF-α, interleukin-1β (IL-1β), lipid peroxidation products, reactive oxygen species/reactive nitrogen species (ROS/RNS), and it reverses lipopolysaccharide-induced motility disturbances; in developing retina, MLT prevents retinal ganglion cell death through its antioxidant and anti-inflammatory properties. In particular, MLT appears as a very interesting drug to reduce the neurological sequelae from hypoxic-ischemic brain injury. Because of its lipophilic properties, MLT easily crosses most biological cell membranes, including the placenta and the blood–brain barrier and may prevent neonatal brain injury in early stage of life. The neuroprotective role of MLT calls for further investigation in the newborn infants.
Keywords: melatonin; oxidative stress; newborn; neuroprotection